Neutrophil‐Related Gene Expression and Low‐Density Granulocytes Associated With Disease Activity and Response to Treatment in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis. Issue 7 (July 2015) - Grayson, Peter C.; Carmona‐Rivera, Carmelo; Xu, Lijing; Lim, Noha; Gao, Zhong; Asare, Adam L.; Specks, Ulrich; Stone, John H.; Seo, Philip; Spiera, Robert F.; Langford, Carol A.; Hoffman, Gary S.; et al.
<x xml:space="preserve">Abstract</x> Objective To discover biomarkers involved in the pathophysiology of antineutrophil cytoplasmic antibody–associated vasculitis (AAV) and to determine whether low‐density granulocytes (LDGs) contribute to gene expression signatures in AAV. Methods The source of clinical data and linked biologic specimens was a randomized controlled treatment trial in AAV. RNA sequencing of whole blood from patients with AAV was performed during active disease at the baseline visit and during remission 6 months later. Gene expression was compared between patients who met versus those who did not meet the primary trial outcome of clinical remission at 6 months (responders versus nonresponders). Measurement of neutrophil‐related gene expression was confirmed in peripheral blood mononuclear cells (PBMCs) to validate the findings in whole blood. A negative‐selection strategy isolated LDGs from PBMC fractions. Results Differential expression between responders (n = 77) and nonresponders (n = 35) was detected in 2, 346 transcripts at the baseline visit (P < 0.05). Unsupervised hierarchical clustering demonstrated a cluster of granulocyte‐related genes, including myeloperoxidase (MPO) and proteinase 3 (PR3). A granulocyte multigene composite score was significantly higher in nonresponders than in responders (P < 0.01) and during active disease than during remission (P < 0.01). This signature strongly overlapped an LDG signature identified previously in lupus (false discovery rate by gene set enrichment analysis <0.01). Transcription of PR3 measured in PBMCs was associated with active disease and treatment response (P < 0.01). LDGs isolated from patients with AAV spontaneously formed neutrophil extracellular traps containing PR3 and MPO. Conclusion In AAV, increased expression of a granulocyte gene signature is associated with disease activity and decreased response to treatment. The source of this signature is likely LDGs, a potentially pathogenic cell type in AAV.